The effect of red wine consumption on health - Mateusz Rzeszutko; Patrycja Szponarowicz; Przemysław Raczkiewicz; Bartosz Snopkowski; Mateusz Skrętowicz; Tomasz Korzec; Jakub Sosnowski; Eliasz Panek; Damian Jasłowski; Dominika Panasiuk (Journal of Education, Health and Sport, 2023)
Introduction and purpose of the study: The impact of red wine consumption on the human body has been the case of research by many scientists. The aim of this study is to review the literature, present the most important research findings, and summarize the current knowledge about wine and other alcoholic beverages consumption.